The British Library's Vulnerable Collection Items Project - Kowal, Kimberly C.; Rhatigan, John (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The British Library embarked on a project in 2007 to better protect collection materials considered vulnerable. Following thefts of maps contained within books, a methodology was developed to firmly identify the unique copies of rare and valuable British Library holdings, using a range of security photography and copy-specific descriptive metadata. The outcome of the project not only served to improve the security of the selected maps, but by revealing these hidden collections, access to and knowledge of them is enhanced.